Answer:
h(x)
Step-by-step explanation:
to solve for an inverse, you swap the x and the y and then solve for y
f(x) = 4x^3-8
y = 4x^3 - 8
x = 4y^3 - 8 swap the x and y
now solve for y:
x + 8 = 4y^3
(x + 8)/4 = y^3
1/4x + 8/4 = y^3
1/4x + 2 = y^3
y = ![\sqrt[3]{1/4x + 2}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B1%2F4x%20%2B%202%7D)
Answer:
It will equally 2 because you need to change the 3 into a 9 because you can't add fractions without having the same common demometer
Step-by-step explanation:
An expression is defined as a set of numbers, variables, and mathematical operations. The solution of (4 x 3)² ÷ 6 is 24.
<h3>What is an Expression?</h3>
In mathematics, an expression is defined as a set of numbers, variables, and mathematical operations formed according to rules dependent on the context.
The solution of the expression (4 x 3)² ÷ 6 is,
(4 x 3)² ÷ 6
= (12)² ÷ 6
= 144 ÷ 6
= 24
Hence, the solution of (4 x 3)² ÷ 6 is 24.
Learn more about Expression:
brainly.com/question/13947055
#SPJ1
Answer:
8 spoons and 9 forks
Step-by-step explanation:
2 F + 1.2S = 27.60
6 F + 5.5S = 98
solve system of equations
Answer:
i got 485!
Step-by-step explanation:
multiply 40 by $15 = 600 then subtract 10% = 540 then subtract 7.5% = 499.5 lastly subtract 2.9% = 485 and that's his take home money :)